The summer book - Jansson, Tove (New York Review Books classics., 2008)
"This brief novel tells the story of Sophia, a six-year-old girl awakening to existence, and Sophia's grandmother, nearing the end of hers, as they spend the summer on a tiny unspoiled island in the Gulf of Finland."--Publisher's description.